Engaging 'communities': anthropological insights from the West African Ebola epidemic. (10th April 2017) - Wilkinson, A.; Parker, M.; Martineau, F.; Leach, M.
Abstract : The recent Ebola epidemic in West Africa highlights how engaging with the sociocultural dimensions of epidemics is critical to mounting an effective outbreak response. Community engagement was pivotal to ending the epidemic and will be to post-Ebola recovery, health system strengthening and future epidemic preparedness and response. Extensive literatures in the social sciences have emphasized how simple notions of community, which project solidarity onto complex hierarchies and politics, can lead to ineffective policies and unintended consequences at the local level, including doing harm to vulnerable populations. This article reflects on the nature of community engagement during the Ebola epidemic and demonstrates a disjuncture between local realities and what is being imagined in post-Ebola reports about the lessons that need to be learned for the future. We argue that to achieve stated aims of building trust and strengthening outbreak response and health systems, public health institutions need to reorientate their conceptualization of 'the community' and develop ways of working which take complex social and political relationships into account. This article is part of the themed issue 'The 2013–2016 West African Ebola epidemic: data, decision-making and disease control'.